Desarrollo de una propuesta de mejora para la planta de tratamiento de aguas residuales de la empresa de lácteos Inversiones Fasulac LTDA (2017)
In the present work of degree was made the diagnosis of both the process and the operation of the company's WWTP, later the corresponding sampling for the characterization in external laboratory was executed and the results of the analyzes showed the non-compliance of the current normativity of the parameters of fats and oils, BOD5 and COD, yielding as results values in the raw water of 1034 ppm, 10 082 ppm and 25 078 ppm respectively. In order to solve the problem, a bibliographic review was carried out in order to determine the alternatives for improvement that were adjusted to the needs of the company and to achieve the removal, in order to comply with resolution 0631 of 2015.